2021
DOI: 10.1111/jopr.13457
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Preparation Depths for an Inlay‐Retained Fixed Partial Denture on the Accuracy of Different Intraoral Scanners: An In Vitro Study

Abstract: Purpose The aim was to evaluate the effect of different preparation depths for inlay‐retained fixed partial dentures on the accuracy of intraoral scanners. Materials and Methods Tooth preparations for two inlay‐retained fixed partial dentures were done and divided according to depth of the preparation. Group A: 2 mm pulpal floor depth, 3 mm gingival floor depth and Group B: 3 mm pulpal floor depth, 4mm gingival floor depth. The CEREC Omnicam 4.4.4, Omnicam 4.6.2. Trios3 and Medit i500 intraoral scanners were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…This superiority was observed by several earlier studies, [11][12][13] and was attributed to the confocal microscopy scanning mechanism of TS, which is assumed to be a more accurate triangulation-based mechanism of MT and OC. [11][12][13] However, this is negated by other studies that did not show similar accuracy patterns. [1][2][3]24 Nevertheless, the TS may have the advantages of being a relatively newer system than the other IOS systems, which may have contributed to easier scanning, more userfriendliness, superior hardware, scanning time, and image resolution.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…This superiority was observed by several earlier studies, [11][12][13] and was attributed to the confocal microscopy scanning mechanism of TS, which is assumed to be a more accurate triangulation-based mechanism of MT and OC. [11][12][13] However, this is negated by other studies that did not show similar accuracy patterns. [1][2][3]24 Nevertheless, the TS may have the advantages of being a relatively newer system than the other IOS systems, which may have contributed to easier scanning, more userfriendliness, superior hardware, scanning time, and image resolution.…”
Section: Discussionmentioning
confidence: 74%
“…The comparison among the different IOS systems indicated that the TS was clearly more precise than MT and OC, respectively. This superiority was observed by several earlier studies, 11–13 and was attributed to the confocal microscopy scanning mechanism of TS, which is assumed to be a more accurate triangulation‐based mechanism of MT and OC 11–13 . However, this is negated by other studies that did not show similar accuracy patterns 1–3,24 .…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The higher the depth of the pulpal and gingival floors of a tooth preparation, the higher the discrepancy or lower scanning accuracy values reported. 33,35 The finish line location of a tooth preparation significantly affects the scanning accuracy values (Figure 2). 25,28,31 Therefore, the apicocoronal position of the tooth preparation finish line may impact the accuracy of the intraoral digital acquisition procedure.…”
Section: Surface Characteristicsmentioning
confidence: 99%